Sputter-deposited AlN coatings for enhanced tarnish resistance and mechanical durability of silver jewelry - Sudsawad, Kanyarat; Somjaijaroen, Natthawirot; Somdock, Nuttakrit; Sakdanuphab, Rachsak; Sakulkalavek, Aparporn; Rudradawong, Chalermpol (My University, 2026)
Silver jewelry is prone to surface tarnishing caused by sulfur-containing species in ambient environments. In this study, a transparent aluminum nitride–based thin film was deposited by magnetron sputtering and evaluated as a protective barrier against silver tarnishing. Sheets of 99.9% pure silver were coated under various nitrogen flow conditions to optimize film composition and performance. An appropriate nitrogen flow rate of 25 standard cubic centimeters per minute (sccm), corresponding to an N₂/Ar gas ratio of approximately 1:1, was identified for forming AlN-rich films, while an AlN-based film thickness in the range of 80–110 nm was found to be suitable for jewelry protection. X-ray photoelectron spectroscopy analysis showed that insufficient nitrogen availability suppresses complete nitridation, resulting in residual metallic aluminum, which readily reacts with residual oxygen and moisture, increasing the oxygen content in the films. At an N₂ flow rate of 25 sccm, metallic aluminum was suppressed and the films were dominated by Al–N bonding with minor oxygen incorporation, accompanied by the development of a polycrystalline structure. Nanoindentation measurements performed on the 110 nm-thick film yielded a peak hardness of approximately 3.6 GPa, indicating enhanced mechanical durability compared with uncoated silver. Comparative evaluation of color difference, mechanical hardness, tarnish resistance, and environmental durability demonstrated improved performance of the AlN-coated silver. Finally, the practical applicability of the coating was demonstrated by depositing AlN-based films onto large and intricately designed silver jewelry items, indicating compatibility with industrial-scale processing.
Keywords: Aluminum nitride; Magnetron sputtering; Silver; Tarnish; Thin films